Exploring the Role of Gen Z Women: A Case Study of Aqeela in the Television Drama Asmara Gen Z - Faridha Noer Barkah; Chania Pitrisia (Women, Education, and Social Welfare, 2025)
This study investigates the representation of Gen Z women in Indonesian television drama through a case study of Aqeela in Asmara Gen Z. The research addresses the growing importance of media in shaping perceptions of gender and youth identity, particularly among female Gen Z who negotiate between traditional expectations and modern aspirations. Using a qualitative research design, the study applied content analysis and Barthes’ semiotic approach to ten purposively selected episodes that highlight Aqeela’s character development. The analysis revealed a clear transformation in Aqeela’s portrayal: from an empathetic and caring figure in the early episodes, to a reflective and assertive individual in relational contexts, a socially engaged leader in collective settings, and ultimately an empowered character capable of confronting injustice. These findings demonstrate that Indonesian sinetron can function not only as a medium of entertainment but also as a cultural text that negotiates gender roles and articulates hybrid identities of young women. The study contributes to media and gender scholarship by offering evidence of how television narratives can construct multidimensional female characters, and it provides practical implications for educators and media practitioners to use popular culture as a platform for discussing gender equality and youth empowerment.